Digital Transformation in Indonesian Maritime Education: A Qualitative Study on Technology-Enhanced Learning - Elis Kardiono, Devega (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STIP Jakarta, 2025)
This research critically examines the integration of digital technologies in maritime education at Sekolah Tinggi Ilmu Pelayaran (STIP) Indonesia and its impact on graduate competency development. Through a qualitative approach involving in-depth interviews with graduates, educators, and industry stakeholders, along with document analysis, the study reveals a significant